E-WOM dan Keputusan Pembelian Produk Fashion di Shopee - Nieldya Nofandrilla (Departemen Ilmu Komunikasi Universitas Andalas, 2025)
Electronic Word of Mouth (e-wom) refers to a marketing communication approach that involves the dissemination of recommendations for goods and services through social media or e-commerce platforms. The objective is to exert influence on prospective shoppers by directly perusing reviews of purchasers' experiences. The purpose of this study is to examine the impact of e-wom on the purchasing decisions of millennials in the Solo Raya region when it comes to fashion products available on the Shopee Marketplace. This research makes a significant contribution to the advancement of e-commerce in the fashion industry, particularly by enhancing our understanding of how customer behaviour is influenced by reviews. A total of 155 respondents were surveyed using questionnaire. The independent variables used to assess e-wom include intensity, positive valence, and content. The dependent variable indicators (Y) used to assess purchasing decisions include product selection, brand selection, purchase timing, purchase quantity, and payment method. The research finding indicates that e-wom has a substantial and favourable impact on the decision-making process when it comes to purchasing fashion products from Shopee. The three e-wom indicators collectively serve as the foundation for decision-making when purchasing items on Shopee.